Strategi Peningkatan Kualitas Pelayanan Akademik pada Perguruan Tinggi - Solekhul Amin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2017)
The success of an educational organization in achieving its intended purpose can not be separated from the service quality and management of price or cost to achieve one goal is to give satisfaction to the academic. This study aims to analyze the influence of quality of service to academic satisfaction college student, the influence of price on students 'academic satisfaction, and influence jointly between quality and price sevice on students' academic satisfaction. Techniques analysis of the results of studies using dekspriptif. Based on this study suggested satisfaction of students' academic needs to be improved because there are still some students who are not satisfied with the service quality and price or cost they have paid. Positive effect that if the quality of service and better pricing management in then increasing students' academic satisfaction.